Pengaruh Kompos Kotoran Sapi dan Mulsa Jerami Padi terhadap Pertumbuhan dan Hasil Polong Muda Kedelai Edamame (Glycine max (L) Merill) di Lahan Kering - SUDARMINI, NI KETUT; KARTINI, NI LUH; SUDARMA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 5 No 2 (2015), 2015)
Effects of Cow Manure Compost and Paddy Straw Mulch on the Growth and Yield ofYoung Pods of Edamame Soybean ( Glycine Max (L) Merill ) in The Dry Land. The loworganic matter in soil is one of the factors causing low levels of soil fertility. The use ofcomposted cow manure and paddy straw mulch can increase nutrient uptake in soybeanplants. The aim of this study was to determine the effect of cow manure compost and paddystraw mulch on the growth of Edamame soybeans in dry land. This experiment used factorialrandomized block design (RBD). The research was conducted from March to June 2015 inDenpasar. The result of the study showed that the application of cow manure compost andpaddy straw mulch at 5 t.ha-1 each gave a significant interaction on the components of growthand yield, produced 21.67 kg of young pods. plot-1 and 10.83 tons ha-1. In the single factor,compost of 5 t.ha-1 produced 19.63 kg of young pods. plot-1 and 9.82 tons ha-1. Paddy strawmulch of 5 t.ha-1 resulted in 15.87 kg young pods plot-1, and 7.93 tons ha-1. High yieldpotential between the two factors was influenced by an adequate availability of nutrients.
Keywords: cow manure compost; paddy straw mulch; soybean; dry land